Effect of ecobiometric variables in coelomic cavity organs in red-tailed boas - Andrade, Rafael Santos; Rahal, Sheila Canevese [UNESP]; Filho, Ednaldo Silva; Conceição, Maria Eduarda Andrade Bastos Moutinho [UNESP]; Feliciano, Marcus Antônio Rossi [UNESP]; Teixeira, Dárcio Ítalo Alves; Monteiro, Frederico Ozanan Barros (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2016)
B-mode ultrasound employment in snakes is a challenge because the anatomy is differentiated in relation to birds and mammals. Thus, the present study aimed to describe the topography and ultrasonographic characteristics of the liver, gallbladder, spleen, kidneys, and conduct a comparison of measurements and biometric variables in snakes. Fifty-seven red-tail boas (Boa constrictor) were grouped according to body mass: Group A [30 snakes (15 males and 15 females) with body mass ranging from 0.8 to 2.8 kg] and Group B [27 snakes (12 males and 15 females), body mass ranging from 3 to 3.4 Kg]. Prior to imaging, the red-tail boas received a physical examination to assess for any visible lesions or damage that could compromise their overall condition. The ultrasonographic exams were performed using an ultrasound with convex (3.5 MHz), linear (7.5 MHz), and linear multi-frequency (6-18 MHz) transducers. All ultrasound parameters were performed using sagittal and transverse B-mode. Sex did not influence the biometric parameters evaluated. However, body length and body mass influenced some organs of the coelomic cavity. Ultrasonography is a useful diagnostic tool for the assessment of the snake in red-tailed boas. In addition, data reported in this study are important as a basis for ultrasound examination for other snake species.
Keywords: Biometrics; Snakes; Ultrasound